The Volatility Processes In Indonesia’s Demand For Narrow Money - Syamsul Hidayat Pasaribu (Universitas Islam Indonesia, 2002)
There were two purposes of this research. The first purpose was to test and search the volatility processes by using ARCH/GARCH methodology in Indonesia’s demand for narrow money estimation, which was approached by error correction modeling (ECM). The empirical evidences had shown that the estimation of Indonesia’s demand for narrow money contained the volatility processes (GARCH processes). The second purpose was to prove that the estimation of ECM, which contained the GARCH processes, had the better abilities for prediction than its benchmark. For this pur-pose, the research compared the predictive powers of Root Mean Squared Error (RMSE), Mean Absolute Error (MAE), and Mean Absolute Parentage Error (MAPE). However, the empirical evidences supported the second purpose.Keywords: error correction modeling (ECM), volatility processes, ARCH, GARCH, narrow money.